The Thyroglobulin paradox; An enigmatic case report of thyroid carcinoma with skeletal metastasis (Bangladesh Journal of Nuclear Medicine, 2026)
Thyroglobulin (Tg) is frequently measured in follow-up of patients with differentiated thyroid carcinoma after total thyroidectomy and radioiodine therapy. A low stimulated Tg level (